Authenticity of foods of plant origin - Kotsanopoulos, Konstantinos (U.S.A Taylor and Francis Group, 2021)
"Food is adulterated mainly in an attempt to gain additional profit or due to negligence. It can be damaging to the food industry and economies and can have consequences on food safety and quality. It also undermines consumer trust, which is generally very hard to reverse. A number of techniques, methodologies, systems and technologies have been developed, improved and combined over time to assist in authenticating food and verifying its quality and associated claims. Foods of plant origin are the source of nutrients for billions of people around the globe. Due to the huge variety of plants, and the lack of visual characteristics as a result of processing, advanced techniques are required to detect adulteration"--
Keywords: Vegetables -- Inspection; Fruit -- Inspection; Food adulteration and inspection; Food -- Analysis